“Folkalising” convicts: a “Botany Bay” ballad and its cultural contexts. - Garvey, Nathan (Journal of Australian Studies, 2014)
Widespread interest in Australian folklore and folk music began in the 1950s as a response to the international popularity of the folk revival, led principally by American and British artists and organisations. In revising their own folk traditions, Australian scholars looked to the convict era as an important foundation for the “bush music” that was to follow. Yet, the evidential basis for the oral transmission of convict ballads has been remarkably slim. This essay considers the case of one well-known convict ballad, exploring its evolution through British print culture and its transformation into a “folk” song in the twentieth century.